Pengaruh Return on Asset, Debt to Asset Ratio dan Firm Size Terhadap Effective Tax Rate (Pada Perusahaan Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2019–2025) - Alya Puji Vahira; Kasir Kasir; Devyanthi Syarif; Tjipto Sajekti (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This research examines how Return on Assets (ROA), the Debt-to-Asset Ratio (DAR), and company size affect the Effective Tax Rate (ETR) among banking firms listed on the Indonesia Stock Exchange from 2019 to 2025. In this context, the ETR serves as a metric for evaluating corporate tax liabilities. Using a quantitative design, the study collects secondary data from banks annual financial disclosures. The sample was determined through a purposive sampling approach. Statistical computations covering descriptive statistics, classical assumption diagnostics, multiple linear regression, the coefficient of determination, and hypothesis testing (t test and F test). The empirical findings demonstrate that ROA, DAR, and firm size each exert a positive and significant partial effect on the effective tax rate. Furthermore, these three independent variables simultaneously influence the ETR. The coefficient of determination R² = 0,226 reveals that the investigated predictors account for 22,6% of the variance in the effective tax rate, whereas the other 77,4% is driven by external variables not captured in this research framework.